Naḥwa Manhaj Wasatī Fī Al-Tafsīr: Min Al-Wasaṭiyya Ilā Al-Muwāṭana Fī Miḥwar Al-Insāniyya ʿinda Al-Ḥabīb ʿalī Al-Jufrī - Muhammad Makmun; Avif Alfiyah (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
This article aims to explore the concept of Islamic moderation and its role in achieving citizenship through the principle of